Elevated methylmalonic acid, but not vitamin B12, predicts all-cause mortality in hyperlipidemic adults: a prospective cohort study - Gong, Qingtao; Wang, Baiqiang; Li, Leiyang; Zhao, Gongshuang; Li, Chengzhi; Ma, Lianyue; Yang, Hong; Zhang, Xiaojuan; An, Guipeng; Guo, Chenghu (Frontiers in Nutrition, 2026)
ObjectivesDespite lipid-lowering therapy, patients with hyperlipidemia retain significant residual risk. This study investigated the independent and combined associations of serum methylmalonic acid (MMA), vitamin B12, and functional vitamin B12 status with all-cause mortality in this population.MethodsWe analyzed data from hyperlipidemic participants in the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2014. Weighted Cox proportional hazards models were employed to evaluate the relationships between serum MMA, vitamin B12, functional vitamin B12 deficiency (defined as elevated MMA despite normal/high B12 levels), and all-cause mortality. Nonlinear associations were examined using restricted cubic splines.ResultsDuring a median follow-up of 6.8 years, 626 deaths occurred. After full adjustment, each unit increase in ln-transformed MMA was associated with a 55% higher mortality risk (adjusted HR = 1.55, 95% CI: 1.30–1.84, p < 0.001), while serum vitamin B12 alone showed no significant association. Notably, participants with functional vitamin B12 deficiency (vitamin B12 > 400 pg./mL and MMA > 250 nmol/L) exhibited the highest risk (adjusted HR = 2.40, 95% CI: 1.70–3.41, p < 0.001).ConclusionElevated serum MMA and functional vitamin B12 deficiency are significantly associated with increased all-cause mortality in hyperlipidemia, whereas serum vitamin B12 level alone lacks independent prognostic value. MMA may serve as a novel biomarker for mortality risk in hyperlipidemia population, highlighting the clinical importance of assessing functional vitamin B12 status.